2023
DOI: 10.1186/s12920-023-01469-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinically relevant combined effect of polygenic background, rare pathogenic germline variants, and family history on colorectal cancer incidence

Abstract: Background and aims Summarised in polygenic risk scores (PRS), the effect of common, low penetrant genetic variants associated with colorectal cancer (CRC), can be used for risk stratification. Methods To assess the combined impact of the PRS and other main factors on CRC risk, 163,516 individuals from the UK Biobank were stratified as follows: 1. carriers status for germline pathogenic variants (PV) in CRC susceptibility genes (APC, MLH1, MSH2, MS… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 58 publications
1
16
1
Order By: Relevance
“…In contrast, studies using individuals from a population-based repository (UKBB) show a different distribution of affected MMR genes, with the vast majority of LS individuals carrying pathogenic variants in the moderate and low penetrance genes MSH6 or PMS2 (Table 4). In a gene-specific analysis, Hassanin et al, found that the modifying effect of the PRS is inversely related to the penetrance of the MMR gene, with the strongest effect in MSH6 and PMS2 carriers 19 , which are clearly underrepresented in the studies of Jenkins et al, 20 and the present. This is in line with hereditary breast cancer, where PRS has proven most relevant as a cancer risk modifier in carriers of pathogenic variants in moderate penetrance genes such as CHEK2, ATM, or PALB2 compared with BRCA1/2 33,34 .…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…In contrast, studies using individuals from a population-based repository (UKBB) show a different distribution of affected MMR genes, with the vast majority of LS individuals carrying pathogenic variants in the moderate and low penetrance genes MSH6 or PMS2 (Table 4). In a gene-specific analysis, Hassanin et al, found that the modifying effect of the PRS is inversely related to the penetrance of the MMR gene, with the strongest effect in MSH6 and PMS2 carriers 19 , which are clearly underrepresented in the studies of Jenkins et al, 20 and the present. This is in line with hereditary breast cancer, where PRS has proven most relevant as a cancer risk modifier in carriers of pathogenic variants in moderate penetrance genes such as CHEK2, ATM, or PALB2 compared with BRCA1/2 33,34 .…”
Section: Discussionmentioning
confidence: 81%
“…CC-BY-NC-ND 4.0 International license It is made available under a is the author/funder, who has granted medRxiv a license to display the preprint in perpetuity. (which was not certified by peer review) and Hassanin et al, 19 ) studies is differences in study design and recruitment strategies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PRS can be a precious tool for risk stratification, particularly in identifying groups of people with extremely high or low genetic risk of developing a specific disease or trait. Moreover, based on our recent work and others, it has become clear that for certain traits high PRS along with rare disease-causing variants can further increase the individuals' risk of developing a disease compared to carriers without a high PRS (4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 95%